A Professional Standards for the Future Palestinian Teacher: Problems and Challenges in the Practices - Mahmoud A Assaf (Universitas Negeri Semarang, 2022)
Despite the scientific and informational progress that has occurred recently in teaching methods and teaching aids, and the severe criticism campaigns against the teacher in recent years as a result of the negative behaviors of some irresponsible teachers, the day will not come when the educational process will dispense with the teacher, his position and his roles, but what kind of teachers we need at this time. Concern for professional standards and academic accreditation for teachers does not mean just the existence of a set of standards set by accreditation and development bodies. Rather, we see the need to rethink the concept of outputs and just consider it a process for measuring individuals’ performance. Rather, it goes beyond that to move to transformative learning and get out of the cycle of stagnation in the world of outputs. The use of standards to form a stable teacher, but rather to find the teacher who is the interlocutor, the facilitator for the learning of his students. In light of this, the idea of ​​this paper came to examine the following aspects: (1) The requirements of the educational system in the post-modern era, (2) Justifications for paying attention to the professional standards of teachers, (3) The most important professional standards for teachers to ensure the quality of education, and (4) Reviewing the first criterion for accreditation and professional development committees and bodies related to the faculty’s ability and efficiency to prepare the teacher. To achieve this purpose, the researcher used the fundamentalist approach based on analysis and interpretation, and clarified the importance of applying the professional standards of the teacher that the colleges of preparation must maintain and market them culturally before starting the implementation process.